The challenging management of a series of 43 infants with Netherton syndrome: unexpected complications and novel mutations. (1st March 2021) - Bellon, N.; Hadj‐Rabia, S.; Moulin, F.; Lambe, C.; Lezmi, G.; Charbit‐Henrion, F.; Alby, C.; Le Saché‐de Peufeilhoux, L.; Leclerc‐Mercier, S.; Hadchouel, A.; Steffann, J.; Hovnanian, A.; et al.
Summary: Background: Netherton syndrome (NS) is a rare disease caused by SPINK5 mutations, featuring variable skin and hair involvement and, in many cases, allergic manifestations with a risk of lethality, particularly in infants. The clinical management of NS is challenging. Objectives: To analyse the clinical manifestations of a cohort of infants with NS managed in a reference centre and to draw up recommendations for management. Methods: We conducted a monocentric analysis of patients with NS. The inclusion criteria were management in our reference centre, a histologically or molecularly confirmed diagnosis of NS and available epidemiological, clinical and laboratory data. Results: A total of 43 patients with NS were included. Hypernatraemia was reported in 23 cases (54%) and associated with a greater likelihood of enteral and/or parenteral nutritional support ( P < 0.001). Moreover, hypernatraemia was more frequent in patients with skin manifestations at birth ( P = 0.026) and in patients bearing the c.153delT mutation in SPINK5 exon 3 ( P = 0.014). The need for enteral and/or parenteral nutritional support was associated with a history of hypernatraemic dehydration ( P < 0.001). Several unexpected extracutaneous complications were recorded, and new mutations were reported. The death rate (9% overall) was higher among the subset of patients bearing the c.153delT deletion. Conclusions: Our data emphasize that neonatal NS is a severe and sometimes lethal multisystem disorder. Patients have a high risk of variable metabolic anomalies (i.e. lethal hypernatraemia) and therefore have major nutritional needs. Cases of NS associated with c.153delT are particularly severe. Unexpected clinical manifestations broadened the phenotypic spectrum of NS. We provide recommendations on the management of the life‐threatening manifestations of NS in neonates based on our multidisciplinary experience.